Ikonologi Gambar Karya Anak TPA An-Nawawi Cikeusal - Syarifah Nur Hajja; Yanti Heriyawati; Supriatna Supriatna (PANTUN: Jurnal Ilmiah Seni Budaya, 2020)
Expressions in the imagination process of making fine art works naturally have a positive impact on children's intellectual, emotional, creative and social development. In this case, art activities are associated with mental health because art activities are a medium for expressing feelings, either sad or happy ones. In drawing activities there is a process of imagination with the innocence of children. Through a unique image, even with minimal knowledge of drawing and coloring techniques, children still produce interesting works. The approach used is the Psychology of Imagination from Jean Paul Satre and Iconology from Erwin Panofsky. The research method used is a qualitative with participatory methods letting children play and express themselves without being directed and commanded. The drawings that TPA An-Nawawi children produced shows that the work uses four images according to Jean Paul Satre: images of consciousness, images of spontaneity, images of imitation, and mental images.Keywords: Imagination, Creativity, Child Image